Development of innovative entrepreneurship in Ukraine - Bondarenko, O. (Економічний вісник Донбасу, 2017)
The article considers the problem of development of innovative entrepreneurship in Ukraine. The modern tendencies of development, both business sector, and its innovatively active part have been analyzed. It was revealed that for the previous years the financial and intermediary sector of the economy, which provides an incomparable level of income incomparable with real production, has received hypertrophied development and practically does not create added value. After all, financial intermediary activities bring relatively high returns, while they are relatively low risk, and the activity of the real sector of the economy - the production sector - has the opposite ratio, that is, it is relatively low-yielding, with a profitability of no more than 5%, but relatively risky. Critically high degree of imbalance in unevenness and imbalance in the structure of sources of financing innovative activities of industrial enterprises is maintained: the share of enterprises 'own funds for financing innovative activities is growing and the share of foreign investors' funds has dropped significantly, which indicates a crisis and high degree of risk and instability of the country's economy and innovative business activities. To overcome technological backwardness due to the disproportions that have developed in innovative entrepreneurship, it is necessary to build a system of technological entrepreneurship. It is expedient to build it using an iterative approach. Proposed 9 steps, which include: determining the priorities for technological development of the country for a long-term period; development of the concept of state policy for the development of innovative goods markets based on the use of the potential of technological entrepreneurship; creation of an effective system of communication between organizations engaged in research and development, among themselves and with other socio-social, entrepreneurial and state institutions, the link between society, the state, science, education and entrepreneurship; the development of a system of cooperation between science and entrepreneurship; creation of technological platforms; introduction of the concept of network interaction, which is an important mechanism for implementing the state policy for the development of innovative goods markets based on the use of the potential of technological entrepreneurship; improvement of development institutions as one of the most important instruments of state policy, stimulating innovation processes and infrastructure development using public-private partnership mechanisms; selection of priority markets for innovative products for building an effective system of technological entrepreneurship; linking STP elements, as well as an institutional basis with priority markets for innovative products. У статті розглянуто питання розвитку інноваційного підприємництва в Україні. Проаналізовано сучасні тенденції розвитку, як підприємницького сектора в цілому, так і його інноваційно активної частини.
Виявлено, що за попередні роки гіпертрофований розвиток отримав спекулятивний (фінансово-посередницький) сектор економіки, що забезпечує непорівнянний з реальним виробництвом рівень доходів та практично не створює доданої вартості. Адже фінансово-посередницькі види діяльності приносять відносно високу прибутковість (торгівля: 15,8%), при цьому відносно низько ризиковані, а діяльність реального сектору економіки – виробничого – має зворотне співвідношення, тобто вона відносно низькодохідна, з рентабельністю не вище 5%, але відносно ризикована. Зберігається низький рівень інноваційності діяльності підприємницьких структур. Зберігається критично високий ступінь диспропорційності щодо нерівномірності та дисбалансу структури джерел фінансування інноваційної діяльності промислових підприємств: зростає част¬ка власних коштів підприємств для фінансування інноваційної діяльності та значно впала частка коштів іноземних інвесторів, що свідчить про кризовий стан і високий ступень ризику та нестабільності економіки країни в цілому та інноваційної підприємницької діяльності зокрема.
Для того, щоб здолати технологічну відсталість внаслідок диспропорцій, що склалися в інноваційному підприємництві, необхідно побудувати систему технологічного підприємництва. Її доцільно будувати, використовуючи ітераційний підхід. Запропоновано 9 кроків, які включають: визначення пріоритетів технологічного розвитку країни на довгостроковий період; розробку концепції державної політики розвитку ринків інноваційних товарів на базі використання потенціалу технологічного підприємництва; створення ефективної системи комунікації організацій, що здійснюють дослідження і розробки, між собою і з іншими суспільно-соціальними, підприємницькими та державними інститутами, сполучною ланкою між суспільством, державою, наукою, освітою і підприємництвом; розвиток системи кооперації науки і підприємництва; створення технологічних платформ; впровадження концепції мережевої взаємодії, яка є важливим механізмом реалізації державної політики розвитку ринків інноваційних товарів на базі використання потенціалу технологічного підприємництва; вдосконалення інститутів розвитку як одного з найважливіших інструментів державної політики, що стимулюють інноваційні процеси та розвиток інфраструктури з використанням механізмів державно-приватного партнерства; вибір пріоритетних ринків інноваційної продукції для побудови ефективної системи технологічного підприємництва; ув’язка елементів СТП, а також інституційного базису з пріоритетними ринками інноваційної продукції. В статье рассмотрена проблема развития инновационного предпринимательства в Украине. Проанализированы современные тенденции развития, как предпринимательского сектора в целом, так и его инновационно активной части. Выявлено, что за предыдущие годы гипертрофированное развитие получил финансово-посреднический сектор экономики, который обеспечивает несравнимый с реальным производством уровень доходов и практически не создает добавленной стоимости. Ведь финансово-посреднические виды деятельности приносят относительно высокую доходность, при этом они относительно низко рискованные, а деятельность реального сектора экономики – производственного – имеет обратное соотношение, то есть она относительно низкодоходна, с рентабельностью не выше 5%, но относительно рискованная. Сохраняется критически высокая степень диспропорций по неравномерности и дисбалансу структуры источников финансирования инновационной деятельности промышленных предприятий: растет доля собственных средств предприятий для финансирования инновационной деятельности и значительно упала доля средств иностранных инвесторов, что свидетельствует о кризисном состоянии и высокой степени риска и нестабильности экономики страны в целом и инновационной предпринимательской деятельности в частности. Для того, чтобы преодолеть технологическую отсталость вследствие диспропорций, сложившихся в инновационном предпринимательстве, необходимо построить систему технологического предпринимательства. Ее целесообразно строить, используя итерационный подход. Предложено 9 шагов, которые включают: определение приоритетов технологического развития страны на долгосрочный период; разработку концепции государственной политики развития рынков инновационных товаров на базе использования потенциала технологического предпринимательства; создание эффективной системы коммуникации организаций, осуществляющих исследования и разработки, между собой и с другими общественно-социальными, предпринимательскими и государственными институтами, связующим звеном между обществом, государством, наукой, образованием и предпринимательством; развитие системы кооперации науки и предпринимательства; создание технологических платформ; внедрение концепции сетевого взаимодействия, которая является важным механизмом реализации государственной политики развития рынков инновационных товаров на базе использования потенциала технологического предпринимательства; совершенствование институтов развития как одного из важнейших инструментов государственной политики, стимулирующих инновационные процессы и развитие инфраструктуры с использованием механизмов государственно-частного партнерства; выбор приоритетных рынков инновационной продукции для построения эффективной системы технологического предпринимательства; увязка элементов СТП, а также институционального базиса с приоритетными рынками инновационной продукции.